Gain-flattened S-band depressed cladding erbium doped fiber amplifier with a flat bandwidth of 12 nm using a Tunable Mach-Zehnder Filter - Zulkifli, Mohd Zamani; Jemangin, M.H.; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2011)
S-band amplification is an important area of optical communications research, focusing on meeting the ever-increasing demands for traffic bandwidth as the C- and L-bands approaches to their limits. In this paper a novel method of providing an S-band optical amplifier with a flat gain-bandwidth is proposed. The proposed method utilizes a Depressed Cladding Erbium Doped Fibre together with a Tunable Mach-Zehnder Filter as to generate a flat amplification bandwidth of 12 nm stretching from 1492 to 1504 nm. The average gain value is approximately 24.21 dB, with a peak to peak fluctuation of 0.83 dB and a noise figure ranges from 7.13 to 10.94 dB for input signals of 1484 to 1510 nm.